The Ih Channel Gene Promotes Synaptic Transmission and Coordinated Movement in Drosophila melanogaster - Hegle, Andrew P.; Frank, C. Andrew; Berndt, Anthony; Klose, Markus; Allan, Douglas W.; Accili, Eric A. (Frontiers in Molecular Neuroscience, 2017)
Hyperpolarization-activated cyclic nucleotide-gated ‘HCN’ channels, which underlie the hyperpolarization-activated current (Ih), have been proposed to play diverse roles in neurons. The presynaptic HCN channel is thought to both promote and inhibit neurotransmitter release from synapses, depending upon its interactions with other presynaptic ion channels. In larvae of Drosophila melanogaster, inhibition of the presynaptic HCN channel by the drug ZD7288 reduces the enhancement of neurotransmitter release at motor terminals by serotonin but this drug has no effect on basal neurotransmitter release, implying that the channel does not contribute to firing under basal conditions. Here, we show that genetic disruption of the sole HCN gene (Ih) reduces the amplitude of the evoked response at the neuromuscular junction of third instar larvae by decreasing the number of released vesicles. The anatomy of the neuromuscular junction is not notably affected by disruption of the Ih gene. We propose that the presynaptic HCN channel is active under basal conditions and promotes neurotransmission at larval motor terminals. Finally, we demonstrate that Ih partial loss-of-function mutant adult flies have impaired locomotion, and, thus, we hypothesize that the presynaptic HCN channel at the neuromuscular junction may contribute to coordinated movement.